Main directions of investment activity of brewing industry - Gmyrya, Sergiy (My University, 2014)
The activation of investment activity of industrial enterprises, which are aimed to provide innovative and ecological security, and to provide the simple reproduction of fixed assets of the enterprise, are the main factors to make breweries in Ukraine more competitive.
Keywords: brewing industry; industrial enterprises; investment activity; пивоварна галузь; промислові підприємства; інвестиційна активність; пивоваренная отрасль; промышленные предприятия; инвестиционная активность